О‘QUVCHILARNING ANALITIK TAFAKKURINI RIVOJLANTIRISH ILMIY PEDAGOGIK MUAMMO SIFATIDA - Tleumuratova, N.M. (SCIENCE and SOCIETY, 2024)
The scientific article theoretically analyzes philosophical, psychological, pedagogical and methodological literature on the development of analytical thinking in students and presents the results. The possibilities for the development of (humanitarian) educational activities for the formation of analytical abilities of high school students are determined, the content and essence of the concepts of “ability”, “analytical abilities”, “analytical abilities of high school students” are considered.